A Critique of Thaddeus Metz's Modal Relational Account of Moral Status. Issue 162 (1st March 2020) - Samuel, Olusegun Steven; Fayemi, Ademola Kazeem
Abstract: This article is a critique of Thaddeus Metz's modal relational approach to moral status in African ethics (AE). According to moral relationalism (MR), a being has moral status if it exhibits the capacity for communal relationship as either a subject or an object. While Metz defends a prima facie plausibility of MR as an African account of moral status, this article provides a fresh perspective to the debate on moral status in environmental and ethical discourse. It raises two objections against MR: (1) the capability criterion inherent in MR is not only exogenous to African thought but also undermines the viability of MR; and (2) MR cannot account for the standing of species populations. Both objections have severe implications for biodiversity conservation efforts in Africa and beyond.